Spontaneous broad ligament haematoma following a normal vaginal delivery - Dheeraj Yalla; Alaka N Nadar; Usha Rani G (Barpeta Obstetrics and Gynaecological Society, 2019)
Broad ligament haematoma is a rare complication of a normal vaginal delivery. We report one such case of a woman who developed this complication within 3 hrs of normal vaginal delivery. Diagnosis was confirmed by clinical features and transabdominal ultrasound. Based on patients haemodynamic instability surgical management in the form of obstetric hysterectomy was done.